Evaluation for heat stress tolerance in durum wheat genotypes using stress tolerance indices. Issue 1 (2nd January 2018) - Kamrani, Morteza; Hoseini, Yaser; Ebadollahi, Asgar
ABSTRACT: Heat stress is a major environmental stress limiting wheat productivity in most cereal growing areas of the world. The objective of this study was to evaluate heat stress tolerance in durum wheat ( Triticum turgidum var. durum) genotypes. For this purpose, 45 genotypes were grown during two growing seasons (2012–2013 and 2013–2014) under non-stress (normal sowing) and heat-stress (late sowing) conditions. The heat tolerance indices were calculated based on grain yield under normal sowing (Yp) and late sowing (Ys) conditions. Results of combined analysis of variance showed the significant influences of heat stress on grain yield as well as significant differences among genotypes for grain yield and the indices. Results of correlation coefficients and multivariate analyses revealed that the stress tolerance index (STI), geometric mean productivity and mean productivity (MP) indices were the most profitable criteria for selection of heat tolerant and high yielding genotypes. Using STI, GMP and MP, the genotypes G29, G41 and G10 were found to be the best genotypes with relatively high yield and suitable for both normal and heat stressed conditions. Based on biplot analysis using Yp, Ys and the indices, it was possible to identify superior genotypes across the conditions.